Fission and properties of neutron-rich nuclei : proceedings of the Fifth International Conference on ICFN5 : Sanibel Island, Florida, USA, 4-10 November 2012 - Hamilton, J. H.; Ramayya, A. V. (World Scientific, 2014)
These proceedings are the fifth in the series of International Conferences covering fission and properties of neutron-rich nuclei, which are at the forefront of nuclear research. The time interval of 5 years between each conference allows for significant new results to be achieved. Recently, world leaders in theory and experiments in research and the development of new facilities for research presented their latest results in areas such as synthesis of superheavy elements, new facilities for and recent results with radioactive ion beams, structure of neutron-rich nuclei, nuclear fission proces.